An Implementation of Measurement System Analysis for IoT-Based Waste Management Development - Heru Wijanarko; Ari Wira Saputra; Ika Karlina Laila Nur Suciningtyas; Rifqi Amalya Fatekha (Jurnal Rekayasa Elektrika, 2022)
A measurement system is a process that consists of standards, employees, and methods for measuring particular quality characteristics. Measurement System Analysis (MSA) attempts to evaluate a measuring system's precision, accuracy, and consistency so that clients receive high-quality goods. The previous study implements the MSA for machinery and industrial lines, electronics manufacturing, agricultural and poultry, aviation, and even employee monitoring and inspection. Elsewhere, waste management has problems, especially with capacity measurement instruments and weight sensors. This study aims to: (i) build an IoT-based waste management system; and (ii) evaluate the developed system by implementing the MSA technique, focusing on measurement equipment. The Gauge Repeatability and Reproducibility (GRR) Study Type 1, the (GRR) Study, and the Analysis of Variance (ANOVA) are conducted to evaluate the measurement instrument of the waste management system. The study findings that the total variance of the GRR is 20.95 %, and the distinct categories are 6. Thus, as the Automotive Industry Action Group (AIAG) GRR recommendation, the measuring system is marginal (acceptable in certain conditions). Moreover, the ANOVA result indicates that interaction and operators did not affect measurement outcomes because the blue dots remain inside the acceptable range.